Integrating Support Services for Student-Athletes: Possible Pathways - Denson, Eric L. (My University, 1992)
Student Services for Athletes (SSA) is a comprehensive, integrated program of support services for student-athletes. The services and components of the SSA program were first briefly described. Then, the value of adopting an integrated approach to support services was discussed, and case examples were used to describe ways in which each component of the SSA model served as a point of intervention, while suggesting how other components are integrated and potentially modified.
Keywords: student development; academic support